Pemanfaatan Limbah Kayu dan Kulit Kopi Menjadi Bahan Bakar Refuse Derived Fuel (RDF) - Wahyudi, Wahyudi; La Ode M. Firman (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2025)
Utilization of coffee skin waste into briquettes as a substitute for biogas to support the roasting process of robusta coffee processing is an alternative energy innovation as a substitute for conventional charcoal from wood and biogas from LPG as well as to support energy security. RDF briquettes are a material that is greatly influenced by the characteristic and type of materials that make up the composition. This research aims to determine the effect of the composition of briquettes with a mixture of coffee husk waste and wood dust on calorific value, water content, ash content and Volatile Matter. The method used is experimental. This research made 5 (five) samples that were carried out with various compositions and tested 3 times each. The results showed that sample 3 produced an average calorific value of 7092 kcal/kg, Water Content 7.87%, Ash Content 7.86%, Volatile Matter 14.73% and Fixed Carbon 15.1%, in accordance with the SNI No.1 / 6235 / 2000 standard for wood charcoal briquettes.